Exploring the natural products chemical space through a molecular search to discover potential inhibitors that target the hypoxia-inducible factor (HIF) prolyl hydroxylase domain (PHD) - Sayaf, Abrar Mohammad; Ullah Khalid, Saif; Hameed, Jawad Ahmed; Alshammari, Abdulrahman; Khan, Abbas; Mohammad, Anwar; Alghamdi, Saeed; Wei, Dong-Qing; Yeoh, KarKheng (Frontiers in Pharmacology, 2023)
Hypoxia-inducible factor (HIF) prolyl hydroxylase domain (PHD) enzymes are major therapeutic targets of anemia and ischemic/hypoxia diseases. To overcome safety issues, liver failure, and problems associated with on-/off-targets, natural products due to their novel and unique structures offer promising alternatives as drug targets. In the current study, the Marine Natural Products, North African, South African, East African, and North-East African chemical space was explored for HIF-PHD inhibitors discovery through molecular search, and the final hits were validated using molecular simulation and free energy calculation approaches. Our results revealed that CMNPD13808 with a docking score of -8.690 kcal/mol, CID15081178 with a docking score of -8.027 kcal/mol, CID71496944 with a docking score of -8.48 kcal/mol and CID11821407 with a docking score of -7.78 kcal/mol possess stronger activity than the control N-[(4-hydroxy-8-iodoisoquinolin-3-yl)carbonyl]glycine, 4HG (-6.87 kcal/mol). Interaction analysis revealed that the target compounds interact with Gln239, Tyr310, Tyr329, Arg383 and Trp389 residues, and chelate the active site iron in a bidentate manner in PHD2. Molecular simulation revealed that these target hits robustly block the PHD2 active site by demonstrating stable dynamics. Furthermore, the half-life of the Arg383 hydrogen bond with the target ligands, which is an important factor for PHD2 inhibition, remained almost constant in all the complexes during the simulation. Finally, the total binding free energy of each complex was calculated as CMNPD13808-PHD2 -72.91 kcal/mol, CID15081178-PHD2 -65.55 kcal/mol, CID71496944-PHD2 -68.47 kcal/mol, and CID11821407-PHD2 -62.06 kcal/mol, respectively. The results show the compounds possess good activity in contrast to the control drug (4HG) and need further in vitro and in vivo validation for possible usage as potential drugs against HIF-PHD2-associated diseases.